Begleitworte zur Karte Cordillera Real Nord (Illampu) 1:50 000 - Ein Beitrag zur kartographischen Darstellung sowie Glaziologie und Gletschergeschichte der bolivianischen Anden - Finsterwalder, Rüdiger; Jordan, Ekkehard (ERDKUNDE, 1989)
The present revision of Troll’s and Finsterwalder’s first mapping from 1928/35 of the Illampu massif of the Cordillera Real/Bolivia is based on preparations lasting several years, and it attempts: 1. To document the glaciological changes which occurred during the last 50 years in the tropics. 2. To complete the invisible areas caused through terrestrial photogrammetry of the original map by using newly-developed aero-photogrammetric methods. 3. To serve official Bolivian cartography as a standard and model for an expressive high mountain relief representation which they aspire to in their basic maps by using representation techniques which are adequate in scale. Therefore in 2 main chapters: 1. The multiple features of the cartographic representation of the new map will be explained on the basis of the photogrammetrie treatment, and 2. The map contents will be dealt with placing the main emphasis on glaciological and glaciomorphological aspects with regard to criteria of the relief and climate configuration of the area represented and of the adjacent area. Referring closely to his comments on the original map, Troll’s pioneer work for tropical glacier research will be underlined and the increase in knowledge based on this century’s methodological and technical progress will be pointed out. In addition, the observations about the snow line, its reconstruction and spatial distribution may be regarded as a contribution to present possibilities of palaeoclimatic research by means of glaciomorphological investigation methods in the tropics, thus indicating modified dynamic processes as compared with the present condition.